PENGUJIAN ASAM LEMAK BEBAS DAN AKTIVITAS MIKROBA PADA BMC-MP-ASI BUAH SUKUN DAN KACANG BENGUK SELAMA PENYIMPANAN - Wisnu Satyajaya; Sri Setyani; Muhammad Nur (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
Free fatty acid and microbial activity of weaning food from bread fruit (Atocarpus communis) and surly bean (Mucuna pruriens L) during storage was evaluated in this research. Variables of research were consisted of duration of storage on 2, 4, 6 and 8 weeks and also the using of polyetylene and alumunium foil. The result showed that product has fulfilled the SNI standard with level of : protein 15.42%, fat 6.74%, fiber 3.375%, water 3.63%, ash content 3.576% and carbohydrate 72.25. During storage, free fatty acid (FFA) level and microba  increased and had significant effects between two kinds of packaging material where alumunium foil tended to have a better effect than that of polyetylene. Keywords : weaning food, bread fruit, slury bean, storage